Application of Attendance Application to the Performance of ASN in the People's Welfare Division, Regional Secretariat of Binjai City - Feby Sahira; Andri Soemitra (Penerbit Jurnal Indonesia, 2022)
Reform of the bureaucracy in Indonesia is assisted by many sectors, one of which is the People's Welfare Section of the regional secretariat. The People's Welfare Section of the Binjai City Secretariat is an element of the regional secretariat staff led by the Section Head, who is located under and responsible to the regional secretariat through government assistants and people's welfare. This research was conducted to see how far the influence of the application of attendance applications on the presence and performance of ASN in the Regional People's Welfare Section of Binjai City. The results showed that the application of the Attendance Application in the People's Welfare Section of the Secretariat of Binjai City was a tool used to achieve effectiveness and discipline in performance. The use of the Attendance Application in the welfare section of the regional secretariat of Binjai City has been proven to affect the performance of ASN. Based on the research that has been done, it is known that the application of the attendance application in the People's Welfare section of the Secretariat of Binjai City has problems such as the internet signal which is sometimes less stable so that ASN has difficulty taking attendance during WFO or WFH.